Experimental Study on Comprehensive Real-Time Methods to Determine Geological Condition of Rock Mass along the Boreholes while Drilling in Underground Coal Mines - Ganggang Niu; Kai Zhang; Bosong Yu; Yanlong Chen; Yu Wu; Jiangfeng Liu (Shock and Vibration)
The geological condition is essential for mining design and disaster control in underground coal mines. The present research focuses on the real-time assessment method on rock mass condition during drilling boreholes. In situ comprehensive experiments were carried out using three methods, which are measurement while drilling (MWD) system, vibration measurement while drilling (VMWD) system, and borehole camera detecting system. In the MWD system, the operating parameters of the drilling machine were recorded, and a dimensionless index Id based on the collected parameters was adopted to assess the geological condition along the borehole. The results show that the state of rock mass can be well classified using the MWD system for both the cross-layer and in-seam boreholes. In the VMWD system, the vibration of the drilling bit was monitored, and the signal was analyzed in both time domain and frequency domain. The results indicate that the rock mass condition can be quantitatively evaluated using the mean square value of the signal and qualitatively estimated using the energy of the spectrum. In the borehole camera system, the photos of the rock mass along the borehole could be well captured, and the identified rock mass condition was used to verify the results of the MWD and VMWD systems. Comprehensive compassion between the results from the three systems shows that all the methods can give valuable information for the geological condition, and the outcomes of the different methods are generally comparable. For practical purposes, the advantages of the involved three detecting systems are discussed.